Two-Photon Fluorescence As Tool For Imaging In Cells - Collado-Martín, Daniel (My University, 2017)
Fluorescent probes are essential tools for studying biological systems. The last decade has witnessed particular interest in the development of two-photon excitable probes, due to their advantageous features in tissue imaging compared to one-photon probes [1]. Recently, we have designed and synthesized an aminonaphthalimide–BODIPY derivative as energy transfer cassette which was found to show very fast and efficient BODIPY fluorescence sensitization [2]. This was observed upon one- and two-photon excitation, which extends the application range of the investigated bichromophoric dyads in terms of accessible excitation wavelengths. In order to increase the two-photon absorption of the system the aminonaphthalimide fluorophore was replaced with a Prodan analogue, which presents a variety of applications as probes and labels in biology [3]. The two-photon absorption cross-section  of the dyads is significantly incremented by the presence of the 6-acetyl-2-naphthylamine donor group. We also explore in this communication the use of new fluorophores based on four-coordinate organoboron N,C-chelates containing an arylisoquinoline skeleton in confocal fluorescence microscopy that show significant two-photon absorption cross sections and allow the use of excitation wavelengths in the near-infrared region [4].References [1] H. M. Kim, B. R. Cho, Chem. Rev. 2015, 5014–5055. [2] D. Collado, P. Remón, Y. Vida, F. Nájera, P. Sen, U. Pischel, E. Perez-Inestrosa, Chem. Asian J. 2014, 9, 797–804. [3] O. A. Kucherak, P. Didier, Y. Mely, A. S. Klymchenko, J. Phys. Chem. Lett. 2010, 1, 616–620. [4] V. F. Pais, M. M. Alcaide, R. López-Rodriguez, D. Collado, F. Nájera, E. Perez-Inestrosa, E. Álvarez, J. M. Lassaletta, R. Fernández, A. Ros, U. Pischel, Chem. Eur. J. 2015, 21, 15369–15376.
Keywords: Flúor -- Efectos fisiológicos; Two phtoton; Fluorophore; BODIPY